SPE Improved Oil Recovery Conference 2020
DOI: 10.2118/200317-ms
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Challenges into Opportunities: First High Salinity Polymer Injection Deployment in a Sour Sandstone Heavy Oil Reservoir

Abstract: This paper describes the design and implementation of a one-spot enhanced oil recovery (EOR) pilot using high-salinity water (∼166,000 ppm TDS) in a sour, sandstone, heavy-oil reservoir (∼5 mol% hydrogen sulfide) based on an extensive laboratory study involving different polymers and operating conditions. In view of the results of this one-spot EOR pilot, a multi-well, high-salinity polymer-injection pilot is expected to start in 2020 targeting the Umm Niqqa Lower Fars (UNLF) reservoir in Kuwait. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Incremental chemical flood costs varied from $18/bbls to $44/bbls depending on the size of the project. The more technical aspect of economically feasible studies can be found in Al-Murayri et al 2018c, 2019c, 2020a. The next report belongs to Dean et al 2018 who provided the cost of both gas and chemical injection.…”
Section: Economic Reportsmentioning
confidence: 99%
“…Incremental chemical flood costs varied from $18/bbls to $44/bbls depending on the size of the project. The more technical aspect of economically feasible studies can be found in Al-Murayri et al 2018c, 2019c, 2020a. The next report belongs to Dean et al 2018 who provided the cost of both gas and chemical injection.…”
Section: Economic Reportsmentioning
confidence: 99%